TI_GERICHTE 12.2007.209 vom 17. Dezember 2008 , Mandato di gestione, diritto di ritenzione, mandato conferito congiuntamente - TI Tribunale d'appello (2008)
Mandato di gestione, diritto di ritenzione, mandato conferito congiuntamente